The way we were [videorecording (DVD)] - Pollack, Sydney, 1934-2008; Streisand, Barbra; Redford, Robert (Columbia TriStar Home Video, 1999)
The romance and marriage of opposites-- the love that binds them together and the differences that tear them apart. A love story from college to Hollywood in the thirties, forties, and fifties.